Natural drying of cassava roots on concrete floors - Best, R.; Ospina Patiño, Bernardo; Fernández, F.O.; Medina, LM (International Center for Tropical Agriculture, 1989)
Study guide to be used as a supplement to the audiotutorial unit on the same topic.